2018
DOI: 10.17344/acsi.2018.4305
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Magnesia Incorporation on Properties of Polystyrene/Magnesia Composites

Abstract: In the present study, the effects of magnesia particles on thermal, dynamic mechanical, morphological, and surface properties of polystyrene resin are investigated. In general, the addition of magnesia particles in polystyrene matrix increases the thermal stability, storage modulus, and wettability, on other hand does not affect the molecular mobility. SEM results showed a limited distribution of magnesia particles in the polystyrene matrix at 15 wt.%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 19 publications
1
8
1
1
Order By: Relevance
“…The second decomposition bands for both copolymers surely belong to the styrene fragments. The onset of the decomposition temperature for the neat polystyrene was reported as 372 °C [31] . However, in our study, the onsets of decomposition temperature for the copolymers were observed as about 325 °C.…”
Section: Resultscontrasting
confidence: 66%
“…The second decomposition bands for both copolymers surely belong to the styrene fragments. The onset of the decomposition temperature for the neat polystyrene was reported as 372 °C [31] . However, in our study, the onsets of decomposition temperature for the copolymers were observed as about 325 °C.…”
Section: Resultscontrasting
confidence: 66%
“…PS with a flat surface is hydrophobic and has a water CA of 94°, while a honeycomb surface has a water CA of 107° due to the increase in surface roughness, 43 and consequently, particles coated with PS have a hydrophobic surface. Hachani et al 44 studied the wettability of PS/magnesia (MgO) composites and observed that the addition of magnesia particles to the PS matrix increased the wettability. That is, while the CA value of PS was 91.5°, this value decreased to 75.5°–86.8° for magnesia composites.…”
Section: Resultsmentioning
confidence: 99%
“…They confirmed that exceeding the temperature of 200 causes the formaldehyde relived from the dimethylene ether groups, which breaks the polymer chain. Thermogravimetric analysis (TGA) for pure PS was conducted by [41]. They confirmed that weight loss reaches 50% at 426.7 • C and 75% weight loss at 437.1 • C. Taking into account the literature data of the UF, PS resin and the obtained results for PLA and PCL, it can be concluded that the lowest thermal stability is achieved by the industrial resin, while PS and PCL weight loss reaches 80% at over 400 • C. DSC curves showed an endothermic melting process at 59.06 • C and 175.25 • C for PCL and PLA, respectively.…”
Section: Resultsmentioning
confidence: 99%